A Meta Analysis of Relationship Marketing And Smes Performance - Ahmed, Mehran (Journal of Mental Health and Social Rehabilitation, 2023)
The objective of the study is to conduct a meta-analysis about relationship marketing which is supposed to be the most successful marketing strategy for the small and medium enterprises. Relationship marketing leads to sustainable cliental for the businesses. Businesses involved in relationship marketing mostly develop long term relations with the consumers which gives long term benefit to the businesses. The findings of the study identified several constructs which needs to be tested empirically.